The essence of play : a practice companion for professionals working with children and young people - Howard, Justine; McInnes, Karen (Routledge, 2013)
"A unique companion to professional play practice! All play professionals are united in their belief that play is important for children's development - and there are inherent characteristics of play that underpin professional play practice across contexts. Providing an overarching concept of play, drawing together the evidence-base across disciplines and linking theory to practice, The Essence of Play is the ideal handbook for all those working with children. Play acts as a natural resource for children to meet physical, intellectual and emotional challenges and this book, unusually, considers play from children's perspectives rather than adults. It provides a baseline of shared knowledge for all play professionals, exploring the fundamental value of play rather than a 'how to' approach to practice. It considers: The therapeutic potential inherent in play; How play reflects and promotes physical, emotional, intellectual, linguistic and social abilities; The emergence of different types of play skills and why these are important; Cross-cultural patterns in play, gender, atypicality and adversity, highlighting the relevance of these issues to professional play practice; The benefits of utilising play for assessment and other professional practice issues such as ethical play practice, balancing risk with health and safety and the creation and management of boundaries. This text is designed for students and practitioners working with children across the helping professions, including early years education, play therapy, playwork, childcare, social care, nursing and allied health. Each chapter will provide directed reading and small reflective tasks to encourage readers to digest key issues"--Vydavatelská anotace
Keywords: hry; dětské hry; terapie hrou; herní specialisté; vývoj dítěte; děti; games; children's games; play therapy; play specialists; child development; children; příručky; handbooks, manuals, etc